2021
DOI: 10.1109/access.2021.3104515
|View full text |Cite
|
Sign up to set email alerts
|

Grayscale Image Colorization Methods: Overview and Evaluation

Abstract: Colorization is a process of transforming grayscale images to color images in a visually acceptable way. The main goal is to convince a viewer in the authenticity of the result. Grayscale images requiring colorization are in most cases images with natural scenes. Over the past 20 years a wide range of colorization methods has been developedfrom algorithmically simple, yet time-and energy-consuming because of unavoidable human intervention to more complicated, but simultaneously more automated methods. Automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Despite a few differences, the existing colorization methods are mainly categorized in the literature [ 9 , 13 ] as user-guided ( Section 2.1 ) and learning-based solutions ( Section 2.2 ), differing in the level of operator intervention.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a few differences, the existing colorization methods are mainly categorized in the literature [ 9 , 13 ] as user-guided ( Section 2.1 ) and learning-based solutions ( Section 2.2 ), differing in the level of operator intervention.…”
Section: Related Workmentioning
confidence: 99%
“…Fully automatic deep-learning techniques have supplanted the more demanding traditional guided approaches, and are currently the most promising and explored methods for the image colorization task [ 13 ]. The following sections present an overview of both categories, reviewing more in-depth recent learning-based approaches and some implementations for the aerial-scale image case ( Section 2.3 ).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The instance model, image-level models [230] and a fusion module are trained in three steps. More reviews on AI colorization can be found in [203] [232]. Style transfer is extracting a texture from the source image domain and transfer it to the target image domain using a deep neural network.…”
Section: Image Editingmentioning
confidence: 99%
“…The instance model, image-level models [230] and a fusion module are trained in three steps. More reviews on AI colourization can be found in [203] [232]. Style transfer is extracting a texture from the source image domain and transferring it to the target image domain using a deep neural network.…”
Section: Image Editingmentioning
confidence: 99%